(untitled) (Journal of Pharmaceutical Negative Results, 2022)
BACKGROUND: Skin disorders in lumbo-sacral region is a frequent entity but not paid attention. In our institution we got frequent referrals regarding contraindication of these dermatoses before spinal anaesthesia. AIM AND OBJECTIVES: To know about various Skin disorders in lumbo-sacral region and predisposing factors for it and classifying them according to indication and contraindications for spinal anaesthesia. METHOD AND MATERIALS: An cross sectional observational study for a period of 6 months where patients with Skin disorders in lumbo-sacral region of all age-groups,irrespective of gender,were enrolled in this study. RESULTS: Of 34 referrals for lumbo-sacral Skin disorders,14 cases were dermatophytosis ,8 were PIH,2 were IGH,2 were leprosy,3 were sweat retention dermatitis,2 were psoriasis,1 was MR,1 was darier,1 was parapsoriasis. CONCLUSION: The lumbo-sacral region is the commonest site of sweat retention.The specialists of other departments were unaware of the nature of the disease and we as a dermatologist should guide them to do their procedures.